The Legacy of John: Second-Century Reception of the Fourth Gospel. Edited by Tuomas Rasimus - Edwards, Mark (The journal of theological studies, 2012)
Second-century taxonomists, fond of triads, would have found it easy enough to make three groups of the twelve contributions to this volume. The first three are reflections on the provenance and gestation of the corpus that has traditionally been ascribed to John the apostle. Raimo Hakola, comparing the epistles with the gospel, finds a diversity in the use of cognate idioms which suggests affinity rather than dependence and attests the manifold character of the Johannine tradition without giving evidence of a schism between interpreters of the gospel.